Smart Cinema and Reincarnation of Camp / Smart cinema и реинкарнация кэмпа - TSYRKUN NINA A. / ЦЫРКУН Н.А. (Наука телевидения, 2022)
The juxtaposition of camp and smart cinema in the context of American filmmaking seems justified since both categories fit into a more general notion of Indiewood, reflecting the culture of irony and parody. I consider three comic book movies with their camp characteristics: 1966 Batman by Leslie H. Martinson and 2016–2018 dilogy, Deadpool by Tim Miller and Deadpool 2 by David Leitch. Leslie Martinson’s Batman is one of the first comic book movies in the stylistics of camp, a concept introduced by Susan Sontag. The Deadpool dilogy can be referred to as smart cinema, aimed at a special form of emotional sensibility of the viewers, which brings smart cinema closer to the notion of camp. However, the excessive redundancy and hyperbolism of Batman is to a greater extent quirky and does not reach the level of smart cinema, which implies a more sophisticated “culture” of irony and parody. Deadpool is constructed as a self-referential, mockingly ironic film that uses the technique of breaking down formulaic clichés by accentuating them. Leveraging the resources of its media universe allowed Marvel to spark viewers’ interest. And by mixing various groups in a specific gaming space, by encouraging the audience to participate in discussions of its products on social networks, the studio went beyond the Hollywood unidirectional marketable filmmaking. Соположение категорий кэмпа и так называемого smart cinema в контексте современного американского кинопроизводства представляется оправданным как вписывающихся в более общее понятие «индивуд», то есть гибрид независимого и голливудского кино, и отражающих культуру иронии и пародии. В статье рассматриваются три кинокомикса («Бэтмен», 1966 и дилогия 2016–2018 годов «Дэдпул» и «Дэдпул 2») с характеристиками кэмпа. «Бэтмен» Лесли Мартинсона вошел в историю как один из первых кинокомиксов в стилистике кэмпа. Дилогию о Дэдпуле можно отнести к категории smart cinema, нацеленных на особую форму эмоциональной восприимчивости зрителя, сближающей smart cinema с понятием «кэмп», введенным американским культурологом Сьюзен Сонтаг с искусственностью и избыточностью которого корреспондировала эстетика технологической эры. Однако чрезмерная избыточность и гиперболичность «Бэтмена» соответствует, скорее, понятию quirky (что означает «причудливый», «эксцентричный»), но не дотягивает до smart cinema, предполагающего более изощренную «культуру иронии» и пародии. «Дэдпул» конструируется как автореференциальный, насмешливо-иронический фильм, использующий прием избавления от формульных клише за счет их акцентирования. Подключив ресурсы своей медиавселенной, «Marvel» активировала интерес зрителей. Стимулировав смешение различных групп в особом игровом пространстве, побудив аудиторию участвовать в обсуждении своей продукции в соцсетях, ее создатели вышли за рамки однонаправленного товарного кинопроизводства.